Phytochemical diversity and antimicrobial properties of methanol extract of several cultivars of Catharanthus roseus using GC-MS - siti samiyarsih; NUR FITRIANTO; ELLY PROKLAMASININGSIH; JUWARNO; JUNI SAFITRI MULJOWATI (Society for Indonesian Biodiversity, 2020)
Abstract. Samiyarsih S, Fitrianto N, Proklamasiningsih E, Juwarno, Muljowati JS. 2020. Phytochemical diversity and antimicrobial properties of methanol extract of several cultivars of Catharanthus roseus using GC-MS. Biodiversitas 21: 1332-1344. Catharanthus roseus (L.) G is an important medicinal plant to evaluate the possibility of novel pharmaceuticals since most of the bacterial pathogens are developing resistance against antibiotics. This research aimed to determine the phytochemical diversity of methanol extract of eight cultivars of C. roseus and to evaluate for possible antimicrobial (antifungal and antibacterial) activities. It is the first research to compare phytochemicals and antimicrobial potential among C. roseus cultivars. The compound obtained was screened by Gas Chromatography-Mass Spectrometry (GC-MS) method. While agar-well disc diffusion method was employed to measure antimicrobial activity against Escherichia coli, Staphylococcus aureus, Aspergillus flavus and Aspergillus niger. Based on GC-MS analysis, a total of 18 significantly different metabolite compounds. The abundances of phytochemical compounds (18 classes total) in each cultivar were Dark Pink (66%), Pink (50%), Purple Pink (44%), Pale Pink (27%), White (44%), Milky White (50%), Whitish pink (50%) and Pinkish Red (55%). The leaves extracts showed antimicrobial activity with inhibition zones ranging from 6.40-22.00 mm and 3.35-8.20 mm, respectively. The best antimicrobial activity against E. coli, S. aureus, A. flavus, and A. niger with the zone of inhibition 16.10±1.67 mm, 22.00±0.33 mm, 6.05±0.67 mm and 8.20±0.50 mm respectively by Dark Pink cultivar.